PRECEPTORSHIP IN IMPROVING THE COMPETENCE OF NEW NURSES IN HOSPITALS: A LITERATURE REVIEW - Jery Pandelaki; Erna Rochmawati (Jurnal Keperawatan dan Kesehatan, 2022)
Introduction: A quality nursing care requires competent nurses, however, nurses who have just graduate are often considered not competent and lack of confidence. The preceptorship program is carried out to improve the abilities and competencies of new nurses. This review aims to evaluate the preceptorship program for new nurses and the impact of the program from available literatures. Objectives: Analysis of factors related to preceptorship in increasing new nurses in hospitals Methods: This review used three data bases including: Pub Med, Science Direct, EBSCO. The keywords used are 'preceptorship', 'novice nurse', 'new nurses', 'competence', and 'turn over'. We included publications in English from 2000-2021. Results: A total of six of the 346 articles were included in the book.359 nurses were involved in the preceptorship program from the selected articles.The length of the teaching program varies, carried out between 6 months – 12 months.The preceptorship program has an internal impact on new nurses and hospitals.New nurses can improve their competence, confidence, communication skills, and ability to improve complex skills.In addition, the preceptorship program also has a managerial impact, including an increase in the retention of new nurses and a reduction in the turnover rate of new nurses. Discussions:The effects obtained from the evaluation and implementation of the preceptorship program consist of two internal effects consisting of increased competence, communication, professional relations, and self-confidence and managerial effects consisting of increased new nurse retention and decreased turnover.This program can be implemented in hospital so that it can improve the quality of nursing services. Keywords: preceptorship, novice nurse, competence, turn over